2002
DOI: 10.1034/j.1600-0854.2002.30807.x
|View full text |Cite
|
Sign up to set email alerts
|

EHD3: A Protein That Resides in Recycling Tubular and Vesicular Membrane Structures and Interacts with EHD1

Abstract: Here we report the characterization of an eps15 homology (EH) domain containing protein designated EHD3. EHD3 was mapped to human chromosome 2p22-23, while the murine Ehd3 homolog was mapped to chromosome 17p21. Both the human and the mouse genes contain a polymorphic (CA) repeat in their 3ƒUTR. One 3.6-kb Ehd3 transcript was mainly detected in adult mouse brain and kidney and at day 7 of mouse development. On the other hand, human tissues exhibited two, 4.2-and 3.6-kb, EHD3 RNA species. They were predominantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
88
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 31 publications
13
88
0
1
Order By: Relevance
“…This result implicates the nucleotide binding state of EHD2 in myoblast fusion. EHD proteins 1-4 contain a central coiled-coil region that mediates oligomerization (39,45). Most recently, the structure of EHD2 was determined where the importance of the nucleotide hydrolysis state was established for its interaction with membrane components (23).…”
Section: Discussionmentioning
confidence: 99%
“…This result implicates the nucleotide binding state of EHD2 in myoblast fusion. EHD proteins 1-4 contain a central coiled-coil region that mediates oligomerization (39,45). Most recently, the structure of EHD2 was determined where the importance of the nucleotide hydrolysis state was established for its interaction with membrane components (23).…”
Section: Discussionmentioning
confidence: 99%
“…The protein appears to be a feature of the endocytic recycling compartment (ERC), as it has been shown to colocalize with transferrin containing recycling vesicles. 28,29 A recent study has demonstrated that RNAi-mediated knockdown of EHD3 in HeLa cells results in the failure of internalized transferrin to localize to the ERC, instead remaining contained in large, peripheral organelles. 30 In the same study, the authors note recent evidence implying that blocking vesicle trafficking to the ERC may, in fact, increase the rate of recycling.…”
Section: Discussionmentioning
confidence: 99%
“…RME-1/mRme-1/EHD1 has been shown to interact with several other proteins that are likely to function with RME-1 during membrane transport processes. EHD1/mRme-1 has been shown to form dimers or hetero-oligomers with the highly related protein EHD3 (14). In addition, EHD1/mRme-1 interacts through its EH domain with an actin-associated protein EHBP1 that, like EHD1/mRme-1 itself, is required for insulinstimulated translocation of the GLUT4 to the plasma membrane (13).…”
Section: Discussionmentioning
confidence: 99%
“…RME-1 has three predicted domains: an N-terminal P-loop nucleotide-binding domain, a central domain predicted to form a coiled-coil, and a C-terminal eps15 homology (EH) 1 domain (10). Yeast two-hybrid analysis suggested that EHD1 selfdimerizes or oligomerizes possibly through the activity of its coiled-coil domain (14,15). EHD1 also forms hetero-dimers or oligomers with EHD3, another member of the mammalian RME-1 protein family (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation